SEROPREVALENCIA DE Brucella sp. EN BOVINOS CRIOLLOS DE CRIANZA EXTENSIVA DE LA PROVINCIA DE PARINACOCHAS, AYACUCHO - Valdivia P., Lesmes (2003)
The objetive of the present study was to determine the seroprevalence of Brucella sp. in creole cattle of the province of Parinacochas, Ayacucho, Perú. Serum samples were collected from cows and heifers of 24 herds (n=385) located in 4 districts (Chumpi, Coracora, Puyusca and Pullo), to detect antibodies against Brucella sp. by the Rose Bengal agglutination test. Seroreactor animals were not found indicating that the area is free of Brucella sp. infection or would have a prevalence less than 4.87%. The results may be due to the effective surveillance programme conducted by the sanitary authorities on internal movement of animals, as well as the prevailing climatic conditions and breeding system, which may be adverse to Brucella sp.